Grammatical structure of the metalanguage lexical-phraseological field in the Russian and English languages - Gutovskaya, Marina S. (Journal of the Belarusian State University. Philology, 2019)
The paper views metalanguage (connected with a reflection over language and speech) lexemes and phrasemes as a unified field of nominative units. It identifies the part of speech classes available in the metalanguage lexical-phraseological field in the Russian and English languages, explores organization of the classes (division into semantical-grammatical subclasses) and their proportion in the field, determines the ratio of lexemes and phrasemes in each class. It indicates that a sort of division of labor in the expression of the categorial meanings takes place between metalanguage lexemes and phrasemes: predominantly lexemes convey the categorial meanings of substance (52 % of substantive lexemes vs 36 % of substantive phrasemes in the Russian material, 57 % of lexemes vs 21 % of phrasemes in the English one) and property of a substance (12 % of adjectival lexemes vs 2 % of adjectival phrasemes in the Russian and English material), chiefly phrasemes – the categorial meanings of process (51 % of verbal phrasemes vs 33 % of verbal lexemes in the Russian material, 74 % of phrasemes vs 30 % of lexemes in the English one) and property of a process (11 % of adverbal phrasemes vs 3 % of adverbal lexemes in the Russian material, 3 % of phrasemes vs 1 % of lexemes in the English one). It concludes that in the language there is a correlation between the type of a categorical meaning and the preferred means of its expression: to nominate substances and properties of a substance one-word (mostly primary, direct, non-expressive) namings are wider used, to nominate processes and properties of a process – multi-word (mainly secondary, figurative, expressive) namings.
Keywords: lexical-phraseological field; metalanguage nominative units; differences between lexemes and phrasemes in the expression of the categorial (part of speech) meanings